2023
DOI: 10.1002/prop.202300074
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Dark Energy Stars within Lower Mass Gap in the Realm of f(Q)$f(Q)$ Gravity

Abstract: The object of this article is to study a new class of dark energy stars in the background of gravity by using the metric potentials proposed by Krori‐Barua [J. Phys. A, Math. Gen. 8:508 (1975)]. To achieve the goal, a quadratic form of as is taken into account for the static spherically symmetric spacetime,`a' being a coupling parameter of gravity. The maximum allowable masses with corresponding radii have been obtained via plots for and 8. The obtained maximum masses from our analysis are found in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…Figure 26 represents ω(r) has a decaying pattern and vanishes on the surface of the star. Also ω ò [0,1] satisfied within the compact objects and hence, it can be concluded this model is well-behaved [77,78].…”
Section: Equation Of State (Eos) Parametermentioning
confidence: 83%
See 1 more Smart Citation
“…Figure 26 represents ω(r) has a decaying pattern and vanishes on the surface of the star. Also ω ò [0,1] satisfied within the compact objects and hence, it can be concluded this model is well-behaved [77,78].…”
Section: Equation Of State (Eos) Parametermentioning
confidence: 83%
“…⎞ ⎠ this metric corresponds to the interior line element in equation (25). The continuity of the boundary ∑ for equation (6) provides the explicit equation [77] [ ] ( ) ds 0. 34…”
Section: Interior and Exterior Schwarzschild Solutionmentioning
confidence: 99%
“…[79] The M − R plot displayed the same behavior, according to. [80,81] Deb et al [82] used the conventional choice of f (R, T) = R + 2𝜒T to examine the impact of the modified f (R, T) gravity on the charged strange quark stars. From the investigation, the authors showed that the compact star system grows more massive and larger in size as 𝜒 values decrease.…”
Section: Maximum Allowable Mass and Radiusmentioning
confidence: 99%